Thermal Debinding Study of Waste Polystyrene as a Sustainable Binder in Metal Injection Molding - Noorzaidy, Nurul Sabrina; Asmawi, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Metal injection molding (MIM) is one of most sought commercial process in making intricate metal parts in bulks quantity. Many researchers commonly used commercial binders in MIM and only a few of them were using recycle materials as a binder. In this study, the usage of waste polystyrene as one of the binder material will be observed. The binder system used is a combination of palm kernel (PK) and waste polystyrene (WP) to produce a “green MIM” technology. The feedstock used to produce green part was made with a mixture of Stainless Steel 316L (SS316L) metal powder with the size of 6µm and a binder system which consist of 60 % waste polystyrene and 40 % palm kernel. Thermal Gravimetric Analysis (TGA) and Differential Thermal Analysis (DTA) were done to identify the degradation and melting temperature of binders. However, this study focuses more on thermal debinding of waste polystyrene in MIM technology. After the process of injection molding and solvent debinding, thermal debinding will be carried out. During this process, three samples were analysed. The thermal debinding of these three sample were conducted by using three different debinding temperature at 500 ℃, 550 ℃ and 600 ℃. The heating rate, dwell time and cooling rate were kept at constant values of 2 ℃/min, 60 minutes and 5 ℃/min respectively throughout the whole debinding process. It was recorded that only sample 3 which was thermally debinded at 600℃ had the brown density of 80.30% which exceeding the theoretical value of 80%. This study revealed that waste polystyrene can be optimally used as a binder material in MIM technology and was able to thermally degraded successfully without problem.